Beyond Citation Rates: A Real-Time Impact Analysis of University of Jaffna Research Publications Using Altmetrics - Janen, T. (University Librarians Association of Sri Lanka, 2025)
Citation based indices are mostly accepted and important indicators for assessing academic performance and research excellence. Citation based evaluation metrics are evaluating the long term effect of a research output. Alternative metrics (Altmetrics) are used as non-traditional metric for assessing the visibility and the societal impact of research publications. The objectives of this study were to evaluate the overall social media visibility and societal impact of research publications from the University of Jaffna using Altmetric data, and to identify how major online platforms and open access status contribute to shaping their Altmetric Attention Scores. The study further sought to compare disciplinary variations in online attention while examining the relationship between Altmetrics and traditional citation-based indicators. Finally, the study aimed to analyze the policy influence of University of Jaffna research outputs by investigating their presence in national and international policy documents. This study adopted a quantitative approach to analyze the online mentions and social media visibility of research publications affiliated to the University of Jaffna using Altmetric data. Analysis of the Altmetric Attention Score (AAS) shows that, University of Jaffna research publications received 2,512 total mentions among those 1,972 mentions from social media, 254 news and blogs, 182 mentions in policy, patents and guidelines etc. Seventy-five (75) publications were mentioned in World Health Organization (WHO) policy sources. Open access publications received more AAS than closed access and among the open access, bronze open access received highest AAS and dimension citation. Trend of AAS shows fluctuating pattern and in general it increased over the time. Among the different social media platforms, X-mentions (formerly Twitter) is a dominant platform to publicize University of Jaffna publications. Psychology (n=25.83) and biomedical clinical sciences (n= 22.03) received highest average AAS it indicates the strong social media interest than other research publications by University of Jaffna. Research output related to psychology also perform well in dimension citation and it reflecting academic impact. It observed that there were considerable mismatches in some research areas that are highly cited academically may not get proportionate attention in Altmetric and vice versa. Highest number of policy mentions were received by article titled Starting Mental Health Services in Cambodia authored by D. J. Somasundara, attached to Faculty of Medicine. Among 15 policies, 6 policies are from WHO. Same article received good number of dimension citation (n=60) and 6 AAS. Article titled War and Suicide in Northern Sri Lanka received the second highest number of policy mentions (n=09) indicating significant influence on policy making. The result significantly shows the usage of research outputs by the national and international level policy documents. It bought as a valuable indicator of real world influence especially these publications have been cited in global health policies published by WHO. This study highlights the multidimensional impact of University of Jaffna research, demonstrating that Altmetrics complement traditional citations by capturing immediate societal and policy influence. The study recommends strengthening open access publishing and researcher engagement on social media while incorporating Altmetrics into institutional evaluations to enhance visibility and societal impact.
Keywords: University of Jaffna; Altmetric Attention Score (AAS); Dimension Citation; Social Media Impact; Societal Impact